Development of an Interactive E-Module for Wired and Wireless Network Technology Learning at SMK Negeri 1 Sijunjung - Hasana Fiddaraini; Heri Mulyono; Bernediv Nurdin (Ali Institute or Research and Publication, 2026)
This study aimed to develop an interactive electronic module (e-module) for the Wired and Wireless Network Technology subject at SMK Negeri 1 Sijunjung and to evaluate its validity and practicality as a digital learning medium in vocational education. The research employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants involved media experts, subject-matter experts, teachers, and Grade XI students of the Computer and Network Engineering program. Data were collected through observations, interviews, validation questionnaires, practicality questionnaires, and student response questionnaires. The collected data were analyzed using descriptive quantitative techniques.The developed e-module was created using Adobe Animate in HTML5 format and integrated multimedia components such as text, images, videos, audio, animations, and interactive exercises. The validation results showed that the e-module obtained a score of 84.03% from media experts and 93.30% from subject-matter experts, indicating that the module was categorized as very valid. The practicality test results showed scores of 93.75% from teachers and 88.52% from students, which were classified as very practical. In addition, student responses indicated that the e-module supported learning engagement, independent learning, and understanding of networking concepts more effectively. These findings indicate that the developed e-module is feasible and practical for use as a digital learning medium in vocational education and can support more flexible and interactive learning activities.